A New Quaternary Structure Epitope on Dengue Virus Serotype 2 Is the Target of Durable Type-Specific Neutralizing Antibodies - E. N. Gallichotte (American Society for Microbiology, 2015)
ABSTRACT Dengue virus serotype 2 (DENV2) is widespread and responsible for severe epidemics. While primary DENV2 infections stimulate serotype-specific protective responses, a leading vaccine failed to induce a similar protective response. Using human monoclonal antibodies (hMAbs) isolated from dengue cases and structure-guided design of a chimeric DENV, here we describe the major site on the DENV2 envelope (E) protein targeted by neutralizing antibodies. DENV2-specific neutralizing hMAb 2D22 binds to a quaternary structure epitope. We engineered and recovered a recombinant DENV4 that displayed the 2D22 epitope. DENV2 neutralizing antibodies in people exposed to infection or a live vaccine tracked with the 2D22 epitope on the DENV4/2 chimera. The chimera remained sensitive to DENV4 antibodies, indicating that the major neutralizing epitopes on DENV2 and -4 are at different sites. The ability to transplant a complex epitope between DENV serotypes demonstrates a hitherto underappreciated structural flexibility in flaviviruses, which could be harnessed to develop new vaccines and diagnostics. IMPORTANCE Dengue virus causes fever and dengue hemorrhagic fever. Dengue serotype 2 (DENV2) is widespread and frequently responsible for severe epidemics. Natural DENV2 infections stimulate serotype-specific neutralizing antibodies, but a leading DENV vaccine did not induce a similar protective response. While groups have identified epitopes of single monoclonal antibodies (MAbs), the molecular basis of DENV2 neutralization by polyclonal human immune sera is unknown. Using a recombinant DENV displaying serotype 2 epitopes, here we map the main target of DENV2 polyclonal neutralizing antibodies induced by natural infection and a live DENV2 vaccine candidate. Proper display of the epitope required the assembly of viral envelope proteins into higher-order structures present on intact virions. Despite the complexity of the epitope, it was possible to transplant the epitope between DENV serotypes. Our findings have immediate implications for evaluating dengue vaccines in the pipeline as well as designing next-generation vaccines.